P135 Lower limb muscle strength and balance in older adults with distal radius fracture: a systematic review. (23rd April 2022) - Forde, Colin; Nicolson, Philippa J. A; Vye, Charlotte; Pun, Jessica C. H; Sheehan, Warren; Costa, Matthew; Lamb, Sarah E; Keene, David J
Abstract: Background/Aims: Distal radius fractures (DRF) are common fall-related fragility fractures disproportionately affecting older females. After a DRF, there is an increased risk of future fragility fractures and functional decline. Systematic review evidence shows balance and muscle strengthening exercises reduce falls in older adults. Despite this, existing DRF rehabilitation trials have mainly focused on upper limb impairments. To inform rehabilitation requirements, we aimed to 1.) compare lower limb muscle strength and balance between older adults with a DRF with age- and sex-matched controls, and 2.) synthesise lower limb muscle strength and balance outcomes in older adults with a DRF. Methods: We searched Embase, MEDLINE and CINAHL (1990 to August 2021). We included randomised and non-randomised controlled trials, and observational studies, that assessed lower limb strength and/or balance in adults aged ≥50 years enrolled within one year after a DRF. Strength and balance had to be assessed using validated instrumented or physical performance measures. Two reviewers independently screened titles and abstracts, and full-text reports of potentially eligible studies. One reviewer extracted data, then checked by another. Two reviewers independently appraised studies using the Cochrane risk-of-bias tool or Newcastle-Ottawa scale. We synthesised results narratively due to heterogeneity. PROSPERO registration: CRD42020196274. Results: Seventeen studies (10 case-control studies, three RCTs and four case-series) including 1112 participants (95% women) with a DRF were included. Participants' mean age ranged from 56 to 73 years; median sample size was 80 (IQR 54-106). Eleven (65%) studies assessed lower limb muscle strength using 10 different methods. Knee extensor strength assessment was most common (5/11 studies) followed by the 30-second and five times sit-to-stand tests (3/11 studies). All studies assessed balance, using 14 different methods. Single leg balance assessment was most common (6/17 studies) followed by functional reach and postural sway (3/17 studies). 5/10 case-control studies assessed lower limb muscle strength. Two studies found cases performed worse than controls during sit-to-stand tests; three studies assessed knee extensor strength with conflicting findings. All case-control studies assessed balance, with cases demonstrating impaired balance compared to controls on some measures. 4/17 studies assessed strength and 6/17 studies assessed balance at multiple timepoints. Over time, strength progressively improved in 3/4 studies but changes in balance were inconsistent across studies. Conclusion: There is some evidence that older adults with a DRF have impaired lower limb muscle strength and balance compared to age- and sex-matched controls, but findings are inconsistent. Synthesis of results was limited by heterogeneity in the design, quality, and assessment methods used in included studies. Large-scale robust case-control and/or prospective observational studies are needed to better establish the rehabilitation requirements for this population. Disclosure: C. Forde: Grants/research support; CF is supported by the NIHR Biomedical Research Centre, based at Oxford University Hospitals Trust, Oxford. P.J.A. Nicolson: Grants/research support; PN is supported by a Versus Arthritis Foundation Fellowship (ref. 22428). C. Vye: None. J.C.H. Pun: Grants/research support; JP received financial support from the NMAHPs Internship Versus Arthritis (Grant reference 22082). W. Sheehan: None. M. Costa: Grants/research support; MC receives grants from NIHR and related health charities. S.E. Lamb: Grants/research support; SL receives grants from NIHR and related health charities. D.J. Keene: Grants/research support; DK is supported by a National Institute of Health Research (NIHR) Postdoctoral Fellowship (ref. PDF-2016-09-056) and by the NIHR Biomedical Research Centre, based at Oxford University Hospitals Trust.